P‐5.2: A gate driver circuit with a‐IGZO TFTs for a 15‐inch AMOLED display. (28th November 2018) - Xue, Yan; Han, Baixiang; Zhang, Liuqi; Nie, Chenglei; Chaw, Gary; Liao, Congwei; Zhang, Shengdong
Abstract : A depletion‐mode amorphous indium‐gallium‐zinc‐oxide thin‐film‐transistor (a‐IGZO TFT) gate driver on array (GOA) integrated circuit has been proposed and fabricated for a 15‐inch active‐matrix organic light emitting diode (AMOLED) display in this work. The depletion‐mode a‐IGZO TFTs were turned off completely due to series‐connected two‐transistor structure and dual low‐voltage‐level power signal. For this reason, the window of Vth shift margin was wide with margin value from −5V to +10V by Spice simulation. Additionally, the proposed GOA circuit exhibited stable high‐voltage output pulse. Subsequently, GOA circuit was placed in a 15‐inch AMOLED display and the performance of the proposed circuit was confirmed.